1983
DOI: 10.1139/o83-078
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of oxytocin receptor concentration in rat uterine explants by estrogen and progesterone

Abstract: Incubation of uterine explants from immature rats with 0.01-100 ng of 17 beta-estradiol/mL resulted in approximately a fivefold increase in the number of oxytocin receptors per milligram of protein in 48 h. This increase was maintained for at least an additional 48 h in the presence of estrogen. When the explants were incubated with 1 microgram progesterone/mL from the outset, the concentration of oxytocin receptors was the same as initial (0 time) levels. The estrogen-induced increase in oxytocin receptor con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 0 publications
0
50
0
2
Order By: Relevance
“…To accommodate this observation while retaining the down-regulation hypothesis it may be postulated that the process of down regulation of the oxytocin receptor requires continued exposure of the uterus to progesterone. The increased turnover of the oxytocin receptor induced by progesterone in expiants of rat uterus in organ culture (Soloff et al, 1983) is consistent with such an effect, but there appear to be no comparable data for the sheep.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To accommodate this observation while retaining the down-regulation hypothesis it may be postulated that the process of down regulation of the oxytocin receptor requires continued exposure of the uterus to progesterone. The increased turnover of the oxytocin receptor induced by progesterone in expiants of rat uterus in organ culture (Soloff et al, 1983) is consistent with such an effect, but there appear to be no comparable data for the sheep.…”
Section: Introductionmentioning
confidence: 95%
“…The major rise in oxytocin receptor at oestrus appears to be closely linked to declining levels of progesterone and the induction of the receptor by oestrogen can be blocked by progesterone both in vivo (Nissenson, Flouret & Hechter, 1978) and in vitro (Soloff et al, 1983); there is therefore evidence that such a mechanism might operate. As reviewed above it appears most likely that oxytocin infusion delays luteolysis through an inhibitory action on PGF-2rx secretion; it is possible, therefore, that oxytocin affects prostaglandin synthesis, perhaps by reducing the availability of substrate to the synthetase, as a result of interacting with the relatively low levels of oxytocin receptor in the uterus on Day 13 of the cycle.…”
Section: Introductionmentioning
confidence: 99%
“…This increased uterine responsiveness to oxytocin occurs in parallel with an increase in the number of uterine oxytocin binding sites in rats [3,21], humans [4], rabbits [13,14] and cows [5]. Corresponding increases in uterine oxytocin receptor (OTR) mRNA expression in late pregnancy and parturition have been reported in rats [11,12,19], humans [9], cows [8] and sheep [24,25].Estrogen stimulates the number of uterine oxytocin binding sites [3,20,22] and OTR mRNA expression in ovariectomized (OVX) virgin rats [11,12]. However, injection of estrogen does not stimulate oxytocin receptor mRNA expression in late pregnant rats or progesterone-primed OVX virgin rats, but is effective only after ovariectomy and removal of progesterone, respectively [17].…”
mentioning
confidence: 91%
“…However, it remains unclear whether the effects of inhalation of cigarette smoke on the expression of OTR mRNA are a direct action on the myometrium or an indirect action via feto-maternal hormonal conditions influenced by cigarette smoke. This uncertainty is based upon the findings that progesterone decreases the levels of uterine OTR mRNA and protein in pregnant rats (Soloff et al 1983), and estrogen increases the levels of OTR in the rat uterus and in human-cultured myometrial cells (Soloff 1975, Adachi & Oku 1995. Additionally, it has been reported that OTR levels are upregulated through progesterone regression, which occurs during luteolysis in the ewe (Hixon & Flint 1987, Zhang et al 1992.…”
Section: Introductionmentioning
confidence: 99%